2021
DOI: 10.1002/ece3.7838
|View full text |Cite
|
Sign up to set email alerts
|

Climatic‐niche evolution with key morphological innovations across clades within Scutiger boulengeri (Anura: Megophryidae)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 118 publications
1
13
0
Order By: Relevance
“…A good starting point under this premise could be achieved by using genetic data generated by previous studies but analyzing them with the approaches and methodologies used here, see 80 , 125 , ideally those containing comprehensive and exhaustive genetic samplings 34 , 118 . In this line, the characterization and analysis of the dimensions that constitute the ecological niche can become a mandatory procedure when attempting to study the dynamics of species with significant levels of population differentiation 58 , 126 . This is important because populations or lineages within a species could have different evolutionary histories, shaped for example, by geophysical processes occurring locally, whose effect can be overlooked if ecological attributes characterized are only analyzed at the species level.…”
Section: Discussionmentioning
confidence: 99%
“…A good starting point under this premise could be achieved by using genetic data generated by previous studies but analyzing them with the approaches and methodologies used here, see 80 , 125 , ideally those containing comprehensive and exhaustive genetic samplings 34 , 118 . In this line, the characterization and analysis of the dimensions that constitute the ecological niche can become a mandatory procedure when attempting to study the dynamics of species with significant levels of population differentiation 58 , 126 . This is important because populations or lineages within a species could have different evolutionary histories, shaped for example, by geophysical processes occurring locally, whose effect can be overlooked if ecological attributes characterized are only analyzed at the species level.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of the realized niche of a species [1] (sensu Grinnell [2][3][4][5], hereafter niche) and how it varies across space and time has received increasing attention in ecological Birds 2022, 3 150 studies, with important implications in evolution, biogeography, and conservation [6][7][8][9][10][11][12][13][14][15]. Many studies have focused on niche evolution in related taxa [16][17][18][19][20][21][22][23], or on niche quantification of alien species to assess their potential as invaders in non-native ranges [24][25][26][27][28][29][30][31][32]. However, niche quantification and change in avian species remain poorly investigated aspects, especially if compared to other research topics (e.g., population trend assessment).…”
Section: Introductionmentioning
confidence: 99%
“…Scutiger boulengeri , an endemic cold-adapted Xizang alpine toad occurring in mountain streams in Xizang (Tibet) ( Hofmann et al, 2017 ), is widely distributed along the eastern and southern slopes of the Qinghai-Xizang Plateau (QTP) at elevations between 2 400 and 5 270 m a.s.l. ( Chen et al, 2009 ; Lin et al, 2021 ). Previous research of this taxon has revealed that three out of six distinct mitochondrial DNA (mtDNA) genetic clades exhibit significant niche divergence and corresponding body size variation ( Lin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Chen et al, 2009 ; Lin et al, 2021 ). Previous research of this taxon has revealed that three out of six distinct mitochondrial DNA (mtDNA) genetic clades exhibit significant niche divergence and corresponding body size variation ( Lin et al, 2021 ). This system facilitating exploration of novel niche space may work synergistically with intrinsic and extrinsic factors driving population structure and the emergence of new phenotypic changes under climate change.…”
Section: Introductionmentioning
confidence: 99%